2012
DOI: 10.1080/14786419.2010.535151
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and cytotoxic activities of leaves, twigs and stem bark ofScutia buxifoliaReissek

Abstract: The antimicrobial and cytotoxic activities of the dichloromethane, ethyl acetate and butanolic fractions from the leaves, twigs and stem bark of Scutia buxifolia were evaluated using the broth microdilution method and the brine shrimp lethality method, respectively. Phytochemical analysis was performed by thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC). The antimicrobial results demonstrated that the strongest effect occurred with the butanol fraction from the twigs and the et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 8 publications
1
11
0
2
Order By: Relevance
“…Mihai et al (2012) also attribute the inhibitory effect of propolis extract again P. larvae to synergism between flavonoids and phenols. These effects are in accordance with previous works that reported the antibacterial activity of S. buxifolia against diverse pathogens as Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis, Saccharomyces cerevisiae, Mycobacterium tuberculosis, Mycobacterium smegmatis and Mycobacterium avium, between others (Boligon et al, 2012b(Boligon et al, , 2012c.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Mihai et al (2012) also attribute the inhibitory effect of propolis extract again P. larvae to synergism between flavonoids and phenols. These effects are in accordance with previous works that reported the antibacterial activity of S. buxifolia against diverse pathogens as Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis, Saccharomyces cerevisiae, Mycobacterium tuberculosis, Mycobacterium smegmatis and Mycobacterium avium, between others (Boligon et al, 2012b(Boligon et al, , 2012c.…”
Section: Discussionsupporting
confidence: 94%
“…This plant has shown to contain four classes of biologically active compounds, namely phenolic compounds (gallic, caffeic and chlorogenic acids), flavonoids (quercetin, quercitrin, isoquercitrin and rutin), alkaloids (scutianines A-M), and triterpenes (b-sitosterol, stigmasterol and lupeol) (Boligon et al, 2009a(Boligon et al, , 2010(Boligon et al, , 2012aMaldaner et al, 2011). Crude extract and fractions of S. buxifolia showed in vitro antioxidant, antimicrobial and antimycobacterial activities (Boligon et al, 2012b(Boligon et al, , 2012c, where polyphenols, flavonoids and alkaloids present in this fractions were associated with this effects (Trevisan et al, 2009;Boligon et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies have revealed the presence of several classes of compounds, such as esterified sterols and terpenoids (Boligon et al, 2010(Boligon et al, , 2014c, flavonoids (Boligon et al, 2009a), and alkaloids (Maldaner et al, 2011;Menezes et al, 1995;Morel et al, 1979Morel et al, , 1998Sierra et al, 1974), among others, which have been described mainly in the leaves and stem bark of Scutia buxifolia. Previous investigations have demonstrated that the extractive solutions and major compounds found in Scutia buxifolia possess antimicrobial (Boligon et al, 2012a(Boligon et al, , 2012bMorel et al, 2005), antiviral , antioxidant (Boligon et al, 2009b), and protective effects against DNA damage (Boligon et al, 2012c). In spite of the widespread use of an infusion of the stem bark of Scutia buxifolia for the treatment of hypertension in folk medicine, there is only one preliminary study describing in vivo hypotensive properties of crude extracts obtained from this plant (Wasicky et al, 1964).…”
Section: Introductionmentioning
confidence: 95%
“…In these regions, an aqueous infusion prepared with stem bark of Scutia buxifolia has been described and widely used in folk medicine for diuretic and antihypertensive purposes (Wasicky et al, 1964). Phytochemical screening of fractions of bark of Scutia buxifolia revealed the presence of cyclopeptide alkaloids (Maldaner et al, 2011), polyphenols and flavonoids in fractions from leaves and stem bark of Scutia buxifolia (Boligon et al, 2012(Boligon et al, , 2009a(Boligon et al, , 2011. Among the few studies that were conducted, alkaloids isolated from Scutia buxifolia displayed in vitro antimicrobial activity (Menezes et al, 1995;Morel et al, 2005;Maldaner et al, 2011), while polyphenols and flavonoids were associated with antioxidant and antymycobacterial activity (Boligon et al, 2011(Boligon et al, , 2009b.…”
Section: Introductionmentioning
confidence: 97%